Analysis the Effect of Profitability, Liquidity and Solvability on the Completeness Financial Statement Disclosures - Anggraeni Anggraeni (Journal of Contemporary Information Technology, Management, and Accounting, 2021)
Disclosure of information in financial reports is a form of company management accountability in facing dynamic business conditions. Financial reports are used as material for evaluation and consideration for stakeholders, so they must be presented in full with the hope of providing accurate information. A financial report is said to be complete if full disclosure or important information has been included in the financial report. Therefore, every company has an obligation to make improvements to financial reports so that the information submitted is right on target and accurate, including Blue Chip companies. The Blue Chip company is a company that has a national reputation, in terms of quality, ability and reliability to operate profitably in various economic situations. Many factors affect the level of completeness of financial statement disclosure, such as profitability, liquidity, and solvency. This study aims to determine the effect of the level of profitability, liquidity and solvency on the completeness of disclosure of Blue Chip company financial statements in Indonesia. In this study, the level of profitability, liquidity and solvency had no effect on the completeness of financial statement disclosures. Research conducted using quantitative methods with a descriptive approach.